SAT0574 Performance of immunoglobulin M and G (IGM and IGG) antibodies against chikungunya virus (CHIKV) by enzyme-linked immunosorbent (ELISA) technique. (15th June 2017) - Rueda, JC; Angarita, J-I; Santos, AM; Saldarriaga, E-L; Pelaez-Ballestas, I; Lόpez-Morales, P; Londono, J
Abstract : Background: CHIKV is suspected based on epidemiological and clinical criteria, however confirmation of the disease is only achieved by laboratory tests. Laboratory diagnosis is made by two approaches: the detection of viral RNA and identification of the specific immune response by serological methods. Serological tests are the most frequently used laboratory methods for the diagnosis of CHIKV. IgM is the first detected antibodies during 4 to 6 days after onset of symptoms followed by IgG. In Colombia, CHIKV's probable cases are not mandatory to be confirmed, so there is no standardization for laboratory confirmation tests Objectives: To evaluate the performance of IgM and IgG antibodies against CHIKV in a cohort of patients with CHIKV Methods: IgM and IgG antibodies against CHIKV were measured by ELISA (AbcamÒ ab177835 and ab177835 anti-chikungunya virus IgM and IgG human ELISA kit, Cambridge, UK) technique in 604 patients with CHIKV suspicion. A typical case of CHIKV with high sensitivity and specificity obtained from a previous study was used as gold standard for diagnosis of CHIKV. Since CHIKV epidemic of 2014–2015 was the first to be reported in our country (Colombia), no second measurements of IgG were needed to confirmed infection. Results: Cut off point for IgG was 14, 3 SU and for IgM was 11, 2 SU. Mean values for IgG was 36, 7 SU (±22, 7) in patients with CHIKV and 8, 6 SU (SD± 6, 3) for IgM. Statistical significance was obtained for both IgG and IgM ( p <0, 0001) when comparing patients with and without CHIKV. Receiver operating characteristic (ROC) curves showed and area under the curve (AUC) of 0, 81 for IgG and 0, 65 for IgM (figure 1 ). Conclusions: Our study revealed a good performance of IgG and regular performance of IgM for the diagnosis of CHIKV in a cohort of CHIKV patients from Colombia's epidemic. Cut off points for both IgG and IgM were measured for future reference. Disclosure of Interest: None declared